Characterization of human skeletal stem and bone cell populations using dielectrophoresis. (6th December 2012) - Ismail, A; Hughes, MP; Mulhall, HJ; Oreffo, ROC; Labeed, FH
Abstract Dielectrophoresis (DEP) is a non‐invasive cell analysis method that uses differences in electrical properties between particles and surrounding medium to determine a unique set of cellular properties that can be used as a basis for cell separation. Cell‐based therapies using skeletal stem cells are currently one of the most promising areas for treating a variety of skeletal and muscular disorders. However, identifying and sorting these cells remains a challenge in the absence of unique skeletal stem cell markers. DEP provides an ideal method for identifying subsets of cells without the need for markers by using their dielectric properties. This study used a 3D dielectrophoretic well chip device to determine the dielectric characteristics of two osteosarcoma cell lines (MG‐63 and SAOS‐2) and an immunoselected enriched skeletal stem cell fraction (STRO‐1 positive cell) of human bone marrow. Skeletal cells were exposed to a series of different frequencies to induce dielectrophoretic cell movement, and a model was developed to generate the membrane and cytoplasmic properties of the cell populations. Differences were observed in the dielectric properties of MG‐63, SAOS‐2 and STRO‐1 enriched skeletal populations, which could potentially be used to sort cells in mixed populations. This study provide evidence of the ability to characterize different human skeletal stem and mature cell populations, and acts as a proof‐of‐concept that dielectrophoresis can be exploited to detect, isolate and separate skeletal cell populations from heterogeneous bone marrow cell populations. Copyright © 2012 John Wiley & Sons, Ltd.